Physicochemical properties and mechanism of solubilised neohesperidin system based on inclusion complex of hydroxypropyl‐β‐cyclodextrin. (23rd November 2022) - Wang, Chunqing; Xia, Na; Yu, Ming; Zhu, Siming
Summary: A solvent method was used to prepare the inclusion compound of neohesperidin (NH) and hydroxypropyl‐β‐cyclodextrin (HP‐β‐CD) to improve the water solubility and thermal stability of NH. The physical and chemical properties and supramolecular structure of the inclusion complex were investigated by UV–vis spectroscopy, FTIR, SEM, TG‐DTG, PXRD, NMR and molecular docking techniques. The results showed that the C‐ring of NH was embedded in the cavity of HP‐β‐CD to form an inclusion complex. The phase has changed significantly, NH is completely dispersed in HP‐β‐CD in an amorphous state, and the two are combined in the form of non‐covalent bonds such as hydrogen bonds or van der Waals forces. Through inclusion of HP‐β‐CD, the solubility of NH in water at 37 °C increased from 161.81 μg ml −1 to 1927.12 μg ml −1, and its stability was also significantly improved. Abstract :